Technical Note on the quality of DNA sequencing for the molecular characterisation of genetically modified plants. (11th July 2018) - ,; Casacuberta, Josep; Nogué, Fabien; Naegeli, Hanspeter; Birch, Andrew Nicholas; De Schrijver, Adinda; Gralak, Mikołaj Antoni; Guerche, Philippe; Manachini, Barbara; Messéan, Antoine; Nielsen, Elsa Ebbesen; Robaglia, Christophe; et al.
Abstract: As part of the risk assessment (RA) requirements for genetically modified (GM) plants, according to Regulation (EU) No 503/2013 and the EFSA guidance on the RA of food and feed from GM plants (EFSA GMO Panel, 2011 ), applicants need to perform a molecular characterisation of the DNA sequences inserted in the GM plant genome. The European Commission has mandated EFSA to develop a technical note to the applicants on, and checking of, the quality of the methodology, analysis and reporting covering complete sequencing of the insert and flanking regions, insertion site analysis of the GM event, and generational stability and integrity. This Technical Note puts together requirements and recommendations for when DNA sequencing is part of the molecular characterisation of GM plants, in particular for the characterisation of the inserted genetic material at each insertion site and flanking regions, the determination of the copy number of all detectable inserts, and the analysis of the genetic stability of the inserts, when addressed by Sanger sequencing or NGS. This document reflects the current knowledge in scientific‐technical methods for generating and verifying, in a standardised manner, DNA sequencing data in the context of RA of GM plants. From 1 October 2018, this Technical Note will replace the JRC guideline of 2016 (updated April 2017) related to the verification and quality assessment of the sequencing of the insert(s) and flanking regions. It does not take into consideration the verification and validation of the detection method which remains under the remit of the JRC.